Assessing Potential Risks of Influenza A Virus Transmission at the Pig–Human Interface in Thai Small Pig Farms Using a Questionnaire Survey. Issue 1 (16th April 2014) - Netrabukkana, P.; Robertson, I. D.; Kasemsuwan, S.; Wongsathapornchai, K.; Fenwick, S.
Summary: Influenza A viruses pose a major public health threat worldwide, especially due to the potential for inter‐species transmission. Farmers could be among the first people to be infected with a novel reassortant virus in a pig herd and may serve as a source of the virus for their communities. In this study, the pig production systems of smallholders in rural Thailand were examined to qualitatively evaluate the potential risks that may contribute to the spread of influenza A viruses. The investigation was based on questionnaire interviews regarding pig farmers' practices and trading activities. We found that extensive pig–human contacts, commingling of pigs and chickens and suboptimal biosecurity practices adopted by farmers and traders may constitute substantial risks for inter‐species influenza virus transmission, thereby posing a threat to pig populations and human public health. The regular practices of using manure as field fertilizer, hiring boars from outside and trading activities could contribute to the potential spread of influenza viruses in the local community. To mitigate the potential risks of influenza A virus transmission and spread in the local community, it is recommended that appropriate public health strategies and disease prevention policies for farmers and traders should be developed including improving biosecurity, encouraging separation of animals raised on farms and minimizing the exposure between pigs and humans. Furthermore, surveillance systems for pig diseases should be targeted around the festival months, and on‐farm identification of pigs should be promoted.